Impacto das otites médias na aquisição da linguagem em crianças - Balbani, Aracy P.s.; Montovani, Jair C. [UNESP] (Sociedade Brasileira de Pediatria, 2003)
OBJECTIVE: To review the literature concerning the impact of otitis media on language acquisitions in children. SOURCES OF DATA: Medline. The following keywords were used for searching: otitis media, hearing, language and children. SUMMARY OF THE FINDING: The hearing loss observed in otitis media may be a result of: 1) structural disorders in the middle ear; 2) ultrastructural lesions and biochemical anomalies in the cochlea or 3) abnormalities in the central auditory pathways. About 50% of cases of secretory otitis media, for instance, are accompanied by mild fluctuating hearing loss. According to the literature, since the first three years of life are critical for language development, children affected by otitis media in this period are at risk for presenting disturbances in language acquisition, behavior and later academic achievement. CONCLUSIONS: The main consequences of otitis media and hearing loss on language acquisition are phonetic and speech articulation problems, as well as impairment of reading comprehension.

OBJETIVO: A incidência das otites médias em crianças tem aumentado consideravelmente nos últimos 20 anos. O objetivo deste trabalho foi revisar artigos sobre o impacto das otites médias sobre a aquisição da linguagem em crianças. FONTES DOS DADOS: Foram selecionados artigos catalogados na base Medline com os descritores otite média, linguagem, audição e criança. SÍNTESE DOS DADOS: A revisão de literatura mostrou que a perda auditiva observada nas otites médias pode ser resultante de: (1) alterações estruturais na orelha média, (2) lesões ultra-estruturais e anormalidades bioquímicas na cóclea, ou (3) alterações nas vias auditivas centrais. Cerca de 50% dos casos de otite média secretora, por exemplo, são acompanhados de perda auditiva leve e flutuante. Os dados de literatura apontam que os três primeiros anos de vida são críticos para o desenvolvimento da linguagem, e crianças com otites médias, nesse período, têm maior risco de apresentar distúrbios na aquisição da linguagem, no comportamento e, futuramente, no aprendizado escolar. CONCLUSÕES: As principais conseqüências das otites médias e da perda auditiva sobre a linguagem nessas crianças são erros fonéticos e de articulação da fala, bem como dificuldade para compreensão da leitura.
Impact of otitis media on language acquisition in children
Keywords: Otitis media; language; hearing; child; Otite média; linguagem; audição; criança